The human herpesvirus-type 8 is not involved in malignant melanoma$nshort communication - Deichmann, Martin; Thome, M.; Bock, Michael; Jäckel, Andreas; Waldmann, Volker; Näher, Helmut (British journal of cancer, 1999)
Malignant melanomas were supposed to harbour the human herpesvirus-type 8 (HHV-8) genome, as melanoma cells were reported to express interleukin-6 and a homologue of interleukin-6 was found in the HHV-8 genome. We therefore investigated 33 primary malignant melanomas by polymerase chain reaction, but could not find this tumorigenic gamma-herpesvirus in any tumour.
Gesehen am 05.05.2021